(untitled) (Docentes 2.0 Journal, 2022)
The sudden appearance of COVID-19 in China in December 2019 and its subsequent spread throughout the world represented an unprecedented global challenge due to its severity and scope. The main objective was to identify the benefits granted by the experiences lived by university professors in Software Engineering after the implementation of various strategies to face this contingency at the Autonomous University of Yucatan, Mexico. The study was carried out under the inductive, positivist paradigm, quantitative approach, non-experimental design, descriptive type, and cross-section. The population consisted of students studying Software Engineering with a non-probabilistic sample of students who took specific subjects for three semesters. Among the instruments analyzed in this study are examination records that correspond to students in the indicated periods and interviews with teachers about the strategies and tools used. Also, guidelines implemented in the university and the strategies and tools used by professors who teach the subjects addressed in this work are described. However, despite some difficulties identified for both students and professors, results obtained by implementing various strategies before, during, and after the pandemic were positive, generating certainty in the university community. Undoubtedly, the pandemic created spaces to reflect on educational processes, Information and Communication Technologies, and the actual situation of the student body to adopt changes and innovations.